Neuroserpin, IL-33 and IL-17A as potential markers of mild symptoms of depressive syndrome in Toxoplasma gondii-infected pregnant women - Silva, Zolder Marinho; Toledo, Débora Nonato Miranda; Pio, Sirlaine; Machado, Bianca Alves Almeida; Santos, Priscilla Vilela dos; Hó, Flávia Galvão; Medina, Yasmim Nogueira; Cordeiro, Paulo Henrique de Miranda; Perucci, Luiza Oliveira; Pinto, Kelerson Mauro de Castro; Talvani, André (Frontiers in Immunology, 2024)
Depressive syndrome (DS) is a common complication during pregnancy and the postpartum period, and is triggered by multiple organic/genetic and environmental factors. Clinical and biochemical follow-up is essential for the early diagnosis and prognosis of DS. The protozoan Toxoplasma gondii causes infectious damage to the fetus during parasite primary-infection. However, in long-term infections, pregnant women develop immune protection to protect the fetus, although they remain susceptible to pathological or inflammatory effects induced by T. gondii. This study aimed to investigate plasma inflammatory biomarkers in pregnant women seropositive and seronegative for T. gondii, with diagnoses of minor and moderate/severe DS. Pregnant women (n=45; age=18-39 years) were recruited during prenatal care at health centers in Ouro Preto, Minas Gerais, Brazil. Participants were asked to complete a socio-demographic questionnaire to be submitted to well-standardized DS scale calculators (Beck Depression Inventory Questionnaire, Edinburgh Postnatal Depression Scale, and Major Depressive Episode Module). Additionally, 4 mL of blood was collected for plasma neuroserpin, CCL2, IL-17A, and IL-33 analysis. Pregnant volunteers with chronic T. gondii contact were all IgG+ (44%; n=21) and exhibited increased plasma IL-33, IL-17A, and neuroserpin levels, but not CCL2, compared to uninfected pregnant women. Using Beck's depression inventory, we observed an increase in plasma IL-17A and IL-33 in women with T. gondii infection diagnosed with mild DS, whereas neuroserpin was associated with minor and moderate/severe DS. Our data suggest a close relationship between DS in pregnant women with chronic T. gondii infection and neurological conditions, which may be partially mediated by plasma neuroserpin, IL-33, and IL-17A levels.